1961
DOI: 10.1063/1.1706353
|View full text |Cite
|
Sign up to set email alerts
|

Shock Initiation of Detonation in Liquid Explosives

Abstract: Experimental studies of the initiation of liquid explosives by strong plane shocks (pressures 50 to 100 kbar) are described. These experiments demonstrate thermal explosion as a result of shock heating in the explosive. When the shock enters the explosive, the explosive is heated. After a delay, detonation in the heated, compressed explosive begins at the interface, where the explosive has been hot longest. The detonation proceeds through the compressed explosive at a velocity greater than the steady state vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

1966
1966
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(71 citation statements)
references
References 11 publications
4
67
0
Order By: Relevance
“…10) followed by vigorous energy release. This type of wave behavior is consistent with the classic description of homogeneous explosive initiation 20 wherein the explosive material is shocked and, after an induction period, a thermal explosion occurs at or near the explosive/driver interface. After the explosion, the high-velocity reactive wave runs forward into the precompressed explosive.…”
Section: Transmitted Wave Profiles: Results and Discussionsupporting
confidence: 69%
“…10) followed by vigorous energy release. This type of wave behavior is consistent with the classic description of homogeneous explosive initiation 20 wherein the explosive material is shocked and, after an induction period, a thermal explosion occurs at or near the explosive/driver interface. After the explosion, the high-velocity reactive wave runs forward into the precompressed explosive.…”
Section: Transmitted Wave Profiles: Results and Discussionsupporting
confidence: 69%
“…In particular, a finding from Figure 6 that the bimolecular methyl nitrate system compresses by 232 on reaching the transition state accords with thermo-hydrodynamic predictions of a maximum compression of condensed explosives by strong shock waves of 25-37.5% (15,19). Similarly, a 5% compression of a single methyl nitrate molecule along the repulsive portion of the curve in Figure 2 to a state isoenergetic with the transition state for bond scission is also consistent with thermohydrodynamics.…”
Section: Discussion Of Resultssupporting
confidence: 56%
“…Since steady detonation in homogeneous or heterogeneous materials is also believed 8 to be a thermal process, it may be suggested that the approximately 1 -I critical thickness found above is of the same magnitude as the reaction zoone thickness in an established lead azide detonation.…”
Section: G Surface Initiation Of Hemicylindersmentioning
confidence: 97%